Metal oxide semiconductor-based Schottky diodes: a review of recent advances - Noorah A Al-Ahmadi (Materials Research Express, 2020)
Metal-oxide-semiconductor (MOS) structures are essential for a wide range of semiconductor devices. This study reviews the development of MOS Schottky diode, which offers enhanced performance when compared with conventional metal-semiconductor Schottky diode structures because of the presence of the oxide layer. This layer increases Schottky barrier heights and reduced leakage currents. It also compared the MOS and metal-semiconductor structures. Recent advances in the development of MOS Schottky diodes are then discussed, with a focus on aspects such as insulating materials development, doping effects, and manufacturing technologies, along with potential device applications ranging from hydrogen gas sensors to photodetectors. Device structures, including oxide semiconductor thin film-based devices, p-type and n-type oxide semiconductor materials, and the optical and electrical properties of these materials are then discussed with a view toward optoelectronic applications. Finally, potential future development directions are outlined, including the use of thin-film nanostructures and high-k dielectric materials, and the application of graphene as a Schottky barrier material.